Peran Pendidikan Agama Dalam Keluarga Sebagai Filter Dampak Negatif Konten Toxic Masculinity Dan Femininity Di Media Sosial - Intan Dewi (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to analyze the role of religious education in families as a filter against the negative impacts of toxic masculinity and toxic femininity content on social media. The development of social media has brought significant changes in the formation of adolescent gender identity and relations, where digital content often reproduces toxic gender stereotypes. This study used a qualitative approach with library research methods. Data were collected through 23 scientific literature sources consisting of journals, books, and previous research results relevant to Islamic religious education, social media, and digital gender construction. Data analysis was conducted using content analysis techniques through the stages of data reduction, categorization, interpretation, and drawing conclusions. The results show that social media has become a primary space for the spread of toxic masculinity and toxic femininity, which impacts adolescent behavior, psychology, and identity. Toxic masculinity encourages dominant, aggressive behavior, and lack of empathy, while toxic femininity gives rise to social pressures regarding beauty standards, self-validation, and body image. Research findings indicate that religious education within the family acts as a moral filter through the instilling of worship habits, religious communication, guidance on social media use, and parental role models in daily life. Religious education also helps foster self-control, digital literacy, and spiritual resilience in adolescents in the face of the influence of digital culture. The concepts of tarbiyah (Islamic education), ta'lim (Islamic study), and ta'dib (Islamic guidance) have proven relevant in developing moderate and moral Muslim character in the digital age. Thus, religious education within the family is a crucial strategy in facing the challenges of a digital culture rife with negative values.